Synthesis and Antimicrobial Activity of Amino Acids Conjugated Diphenylmethylpiperazine Derivatives - K. N. Shivakumara; K. C. Prakasha; D. Channe Gowda (E-Journal of Chemistry)
A series of amino acid conjugated diphenylmethylpiperazine derivatives were synthesized by coupling diphenylmethylpiperazine with different Boc-amino acids using EDCI/HOBt as coupling agent and NMM as base. The synthesized compounds were characterized by 1H-NMR and elemental analysis. The Boc-deblocked derivatives were tested for their antimicrobial activity. We are here reporting that Phe and Trp conjugated diphenylmethylpiperazine showed equally good antibacterial activities as that of conventional antimicrobial drugs.